2006
DOI: 10.1111/j.1365-2672.2006.03000.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of killing of spores of Bacillus subtilis by dimethyldioxirane

Abstract: Aims:  To determine the mechanisms of Bacillus subtilis spore resistance to and killing by a novel sporicide, dimethyldioxirane (DMDO) that was generated in situ from acetone and potassium peroxymonosulfate at neutral pH. Methods and Results:  Spores of B. subtilis were effectively killed by DMDO. Rates of killing by DMDO of spores lacking most DNA protective α/β‐type small, acid‐soluble spore proteins (α−β− spores) or the major DNA repair protein, RecA, were very similar to that of wild‐type spore killing. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Spore resistance to 30% Microcyn TM (and almost certainly the full strength product) is attributed largely to the spore coat that is also important in spore resistance to many other oxidizing agents (Loshon et al . 2001; Young and Setlow 2003; Paul et al . 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spore resistance to 30% Microcyn TM (and almost certainly the full strength product) is attributed largely to the spore coat that is also important in spore resistance to many other oxidizing agents (Loshon et al . 2001; Young and Setlow 2003; Paul et al . 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, while the loss of spore coats reduces spore resistance to many oxidizing agents (including 30% Microcyn TM ) 10‐ to 100‐fold, decoated spores are only two‐ to threefold less resistant to nitrous acid than are intact spores (Loshon et al . 2001; Young and Setlow 2003; Cortezzo and Setlow 2005; Paul et al . 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown how effective different methods of inactivation on endospores can be [31][32][33][34]. Further examination determined in a rather straightforward way, how each treatment affected the characteristic MALDI-TOF-MS spectra of the endospores.…”
Section: Discussionmentioning
confidence: 98%
“…Further examination determined in a rather straightforward way, how each treatment affected the characteristic MALDI-TOF-MS spectra of the endospores. Previous studies have shown how effective different methods of inactivation on endospores can be [31][32][33][34]. They indicate that each bacterial species has its own optimal inactivation parameters (incubation time, temperature, reagent concentration, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of Fe-TAML-TBHP with CTAB for decontaminant of bacterial spores has been separately validated by Setlows group in deactivating Bacillus subtilis spores [65]. A Gram-negative bacterium E. coli strain DH5a was also effectively deactivated on treatment with Fe-TAML-peroxide system.…”
Section: Deactivation Of Microbial Pathogensmentioning
confidence: 92%